G26(P) Gaps in provision of community paediatric primary dental healthcare: a review of the burden of disease presenting to Emergency Departments. (7th April 2014) - Isba, R; Bolton, C; Rowland, AG
Abstract : Background and objectives: In Greater Manchester, children generally have poorer dental health compared to England as a whole. There is some evidence that emergency departments are increasingly being used as provider of dental care, yet many children who present to the paediatric emergency department (PED) with oral/dental conditions may be better treated earlier/elsewhere. Dental health is also an example of how secondary care may play an important part in the paediatric public health agenda. Method: This was a retrospective audit looking at the burden of paediatric (under the age of 16 years) dental and oral disease presenting to a busy, four-site hospital trust in Greater Manchester, England, between April 1st 2012 and March 31st 2013. Results: There were 1131 attendances (1.5% of all PED attendances) with a final code in the "dental/oral" category and 928 of these had a full diagnosis available. Of these 928 children, more than 15% (151) had a diagnosis of "dental abscess" and 167 (18%) a diagnosis of "toothache/loose tooth". The vast majority of children were discharged home with no secondary care follow up and less than 10% of children were admitted. Conclusion: There seems to be a considerable burden of paediatric dental/oral pathology presenting to PEDs, much of which does not require secondary care. Further work needs to be done, in collaboration with dental and public health colleagues, to develop strategies to improve access to the most appropriate source of community-based dental care for these children, and to improve the dental health care of children.